White Bird : A Wonder Story - Palacio, R. J.; Czap, Kevin (New York : Alfred A. Knopf, 2019)
Tells the story of Julian's Grandmère's childhood as she, a Jewish girl, was hidden by a family in a Nazi-occupied French village during World War II and how the boy she once shunned became her savior and best friend.
Includes bibliographical references (pages 217-219).
Keywords: Grandmothers -- Comic books, strips, etc; Jews -- Comic books, strips, etc; Survival -- Comic books, strips, etc; Grandmothers -- Fiction; Jews -- Fiction; Survival -- Fiction; Cartoons and comics; France -- Comic books, strips, etc -- History -- German occupation, 1940-1945; France -- Fiction -- History -- German occupation, 1940-1945; Comics (Graphic novels); Graphic novels